1961
DOI: 10.1017/s0021859600047699
|View full text |Cite
|
Sign up to set email alerts
|

Growth and muscle development of steers implanted with hexoestrol

Abstract: A muscle biopsy technique was employed in an experiment designed to assess the effects of hexoestrol implantation on 2-year-old and 6-year-old Aberdeen Angus steers under New Zealand grazing conditions. This paper reports the results concerning live-weight gains, carcass weights and detailed analyses of samples of m. semitendinosus and associated subcutaneous fat.There was some evidence of an adverse effect of the biopsy operation on the older, less tractable, animals, despite the observation of no apparent ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1962
1962
1974
1974

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Such seasonal variation in the response of grass-fed steers to implanted sex hormones stresses once again the possibility of the growth of New Zealand grazing stock being affected by oestrogenic levels of pasture plants. Everitt and Carter (1961), using dosage levels of 60 mg of implanted hexoestrol in pasture-fed two-year-old Aberdeen Angus steers, and 90 mg in six-year-olds, found that only the younger cattle evidenced a real increase in liveweight gain over three months in the spring. Callow and Finney (1959), in a study of the implantation of 15 mg, 30 mg, or 60 mg of hexoestrol in steers reared under obviously poor, Argentinian, pastoral conditions, concluded that 30 mg gave the optimum response and that the 60 mg dose level may have actually depressed, rather than stimulated, growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such seasonal variation in the response of grass-fed steers to implanted sex hormones stresses once again the possibility of the growth of New Zealand grazing stock being affected by oestrogenic levels of pasture plants. Everitt and Carter (1961), using dosage levels of 60 mg of implanted hexoestrol in pasture-fed two-year-old Aberdeen Angus steers, and 90 mg in six-year-olds, found that only the younger cattle evidenced a real increase in liveweight gain over three months in the spring. Callow and Finney (1959), in a study of the implantation of 15 mg, 30 mg, or 60 mg of hexoestrol in steers reared under obviously poor, Argentinian, pastoral conditions, concluded that 30 mg gave the optimum response and that the 60 mg dose level may have actually depressed, rather than stimulated, growth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work (Everitt and Carter 1961) had shown the fasting losses of similarly-aged cattle implanted with 60 mg hexoestrol to exceed those of untreated steers. To check that observation in this experiment the cattle were yarded at 0800 hours on 21 November 1959, and were fasted, but with access to water, for 31 hours; four liveweights were recorded during this time, and the last of these weights (taken at 1500 hours on 22 November 1959) has been termed the Starved Liveweight.…”
Section: Slaughter and Processingmentioning
confidence: 93%
See 2 more Smart Citations
“…Merkel et al (1954) and Wilson et al (1955) working with swine and cattle, respectively, described surgical procedures by which a sample was excised from the intact muscle. Everitt and Carter (1961) and Bray (1963) used an instrument similar to a cork borer to obtain a muscle sample; whereas, Harris and Bennett (1970) used a "muscle tissue extractor" to sample the semitendinosus and longissimus muscles of cattle. The above biopsy techniques were developed with larger, more mature animals, and thus may not be directly applicable to the young pig.…”
mentioning
confidence: 99%